A Closer Examination of the Academic Benefits of AP - McKillip, Mary E. M.; Rawls, Anita (The Journal of educational research (Washington, D.C.), 2013)
The authors sought to better understand the relationship between students participating in the Advanced Placement (AP) program and subsequent performance on the Scholastic Aptitude Test (SAT). Focusing on students graduating from U.S. public high schools in 2010, the authors used propensity scores to match junior year AP examinees in 3 subjects to similar students who did not take any AP exams in high school. Multilevel regression models with these matched samples demonstrate a mostly positive relationship between AP exam participation and senior year SAT performance, particularly for students who score a 3 or higher. Students who enter into the AP year with relatively lower initial achievement are predicted to perform slightly better on later SAT tests than students with similar initial achievement who do not participate in AP.